Balancing on a tightrope: Coping with concurrent institutional logics in project business. Issue 1 (January 2022) - Ståhle, Matias; Ahola, Tuomas
Highlights: Many firms offer tailored projects as well as standardized equipment simultaneously. Managing multiple concurrent sales logics represents a challenge for many firms. Multiple segmenting, bridging and demarcating practices were identified. Managers need to actively steer interprocess conflicts as well as synergies. Abstract: Many firms simultaneously offer tailored projects and standardized equipment, creating a need to balance between two concurrent—and, at times, conflicting—sales logics. While it is known that larger firms may utilize several strategies to cope with sales logics' conflicting demands, prior research has not adequately addressed how smaller firms address this challenge. Building upon earlier research on managing complexity caused by competing institutional logics and drawing on empirical evidence from a qualitative case study focusing on a firm offering security solutions, we scrutinize how sales of both types of offerings are managed under two sales logics. We show that the firm may utilize several segmenting, bridging, and demarcating practices both at the organizational and individual level to cope with the logics' conflicting demands as well as leverage synergistic relationships between them. The results encourage the utilization of synergies across logics through dynamic practices when concurrently selling two offering.